PATIENTS’ SATISFACTION WITH THE QUALITY OF DERMATOLOGY CONSULTATION OF A TERTIARY CARE HOSPITAL OF PAKISTAN - Rahman, Atiya; Naveed, Tehseen; Zulfiqar, Sumeera; Akhtar, Aisha; Hamid, Andaleeb; Iftikhar, Nadia (Pakistan Armed Forces Medical Journal, 2021)
Objective: To determine the satisfaction rate of dermatology patients, after purposefully improving the consultation skills of residents.Study Design: Mix-method study.Place and Duration of Study: Department of Dermatology, Combined Military Hospital Lahore, from Jan to Sep 2020,Methodology: Empathy informed curriculum was delivered by the consultants and senior registrar prior to the conduction of study as well as an ongoing process to the post-graduate trainees in the department. Patients’ satisfaction with the quality of dermatological consultation was assessed by consultation and relational empathy (CARE) measure. One hundred and seventy six patients were recruited during the study period. Descriptive statistics such as frequencies, means, standard deviations and percentages were determined from the data. Advanced level analysis was done by Pearson’s correlation coefficients to analyse relationships between variables.Results: The mean age of study participant was 39.01 ± SD 19.81 year, with a minimum of 3 years and maximum of 91 years. Ninety two (52.3%) patients were male and 84 (47.7%) were female. The mean consultation and relational empathy score was 40.34 ± SD 8.56 with 16 minimum score and 50 maximum. One hundred and sixty six (94.3%) patients were overall satisfied with the consultation whereas 10 (5.7%) were not.Conclusion: We found high satisfaction rate amongst patients attending dermatology outpatient department. Empathy informed curricula should be emphasized upon to provide holistic patient care.